2020
DOI: 10.1016/j.neuron.2020.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The Parabrachial Nucleus Directly Channels Spinal Nociceptive Signals to the Intralaminar Thalamic Nuclei, but Not the Amygdala

Abstract: Highlights d The ipsi-and contralateral spinoparabrachial pathways are functionally distinct d The ipsilateral spinoparabrachial pathway mediates nocifensive behavior d Tacr1 + neurons in the PBN represent the major target of spinal projection d The PBN relays nociceptive information to the ILN via glutamatergic synapses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 58 publications
9
101
0
Order By: Relevance
“…While lamina I AS neurons have been proposed to transmit sensory-discriminative information and are likely to be impaired in Phox2a cKO mice, a lack of motivation to respond to noxious stimuli-likely due to defects in Phox2a lamina V/LSN neurons-prevents us from testing this hypothesis. Our data, together with earlier studies, implicate lamina V/LSN neurons in directing motivated nocifensive behaviors via the spino-pBil-medial thalamus pathway (Bourgeais et al, 2001;Deng et al, 2020). Our observations are also in line with those made in mice with a loss of Tac1 spinal neurons (Huang et al, 2019), in that approximately 20% of Phox2a Deep neurons express Tac1, and so their loss may affect the transmission of motivational nociceptive information from the spinal cord to the brain.…”
Section: Phox2a As Neuron Function In Supraspinal Nociceptionsupporting
confidence: 91%
“…While lamina I AS neurons have been proposed to transmit sensory-discriminative information and are likely to be impaired in Phox2a cKO mice, a lack of motivation to respond to noxious stimuli-likely due to defects in Phox2a lamina V/LSN neurons-prevents us from testing this hypothesis. Our data, together with earlier studies, implicate lamina V/LSN neurons in directing motivated nocifensive behaviors via the spino-pBil-medial thalamus pathway (Bourgeais et al, 2001;Deng et al, 2020). Our observations are also in line with those made in mice with a loss of Tac1 spinal neurons (Huang et al, 2019), in that approximately 20% of Phox2a Deep neurons express Tac1, and so their loss may affect the transmission of motivational nociceptive information from the spinal cord to the brain.…”
Section: Phox2a As Neuron Function In Supraspinal Nociceptionsupporting
confidence: 91%
“…Nociceptive information is encoded by spinal cord neurons that send a number of specific projections to the brain (Basbaum et al, 2009; Todd, 2010). One example is spinal projection neurons within the superficial layer of the spinal dorsal horn that express the Tacr1 gene (Barik et al, 2020; Chiang et al, 2020; Choi et al, 2020; Deng et al, 2020). To identify direct spino-recipient areas in the brain, we genetically labeled only the spinal Tacr1 neurons with tdTomato fluorescent protein by the triple crossing of Tacr1 Cre , Cdx2 FlpO , and Ai65 (Rosa-CAG-FrtSTOPFrt-LoxSTOPLox-tdTomato; dsTomato ) mice as described previously (Bourane et al, 2015) (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the lateral PBN receives direct nociceptive inputs from projection neurons within the spinal dorsal horn (Barik et al, 2020; Chiang et al, 2020; Choi et al, 2020; Deng et al, 2020). The dorsolateral PBN (PBdl) receives predominantly nociceptive inputs from the spinal cord and then projects to multiple limbic structures, such as the PAG, VMH, and ILN, thereby producing emotional and physiological changes in response to pain signals (Chiang et al, 2020; Deng et al, 2020). Although the PBdl does not directly project to the amygdala, it indirectly sends pain signals to the CeA through the PBel (Deng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBN is an important pain relay station, connecting the upward pain conduction and downward pain regulation [26] . Sensory information about harmful stimuli travels from primary sensory neurons to PBN and then to regions of the brain associated with pain [4,27] . And many studies have reported that CGRP plays an important role in inflammatory pain [28][29][30] , the present study was aimed to evaluate the role of CGRP in pain regulation in PBN of inflammatory rats by harmful thermal and mechanical stimulation, and to investigate the involvement of CGRP receptors.…”
Section: Discussionmentioning
confidence: 99%